Plant traits modulate grassland stability during drought and post‐drought periods - Luo, Wentao; Shi, Yuan; Wilkins, Kate; Song, Lin; Te, Niwu; Chen, Jiaqi; Zhang, Hongxiang; Yu, Qiang; Wang, Zhengwen; Han, Xingguo; Collins, Scott L. (Functional ecology, 2023)
Grasslands are subject to climate change, such as severe drought, and an important aspect of their functioning is temporal stability in response to extreme climate events. Previous research has explored the impacts of extreme drought and post‐drought periods on grassland stability, yet the mechanistic pathways behind these changes have rarely been studied. Here, we implemented an experiment with 4 years of drought and 3 years of recovery to assess the effects of drought and post‐drought on the temporal stability of above‐ground net primary productivity (ANPP) and its underlying mechanisms. To do so, we measured community‐weighted mean (CWM) of six plant growth and nine seed traits, functional diversity, population stability and species asynchrony across two cold, semiarid grasslands in northern China. We also performed piecewise structural equation models (SEMs) to assess the relationships between ANPP stability and its underlying mechanisms and how drought and post‐drought periods alter the relative contribution of these mechanisms to ANPP stability. We found that temporal stability of ANPP was not reduced during drought due to grasses maintaining productivity, which compensated for increased variation of forb productivity. Moreover, ANPP recovered rapidly after drought, and both grasses and forbs contributed to community stability during the post‐drought period. Overall, ANPP stability decreased during the combined drought and post‐drought periods because of rapid changes in ANPP from drought to post‐drought. SEMs revealed that the temporal stability of ANPP during drought and post‐drought periods was modulated by functional diversity and community‐weighted mean traits directly and indirectly by altering species asynchrony and population stability. Specifically, the temporal stability of ANPP was positively correlated with functional divergence of plant communities. CWMs of seed traits (e.g. seed width and thickness), rather than plant growth traits (e.g. specific leaf area and leaf nutrient content), stabilized grassland ANPP. Productivity of plant communities with large and thick seeds was less sensitive to precipitation changes over time. These results emphasize the importance of considering both the functional trait distribution among species and seed traits of dominant species since their combined effects can stabilize ecosystem functions under global climate change scenarios. Read the free Plain Language Summary for this article on the Journal blog.